EFFECTIVE COUGH AND DEEP BREATH DECREASES THE COLONIZATION OF Staphy lococcus aureus IN SECRET OF POST SURGERY PATIENTS WITH GENERAL AENESTHESIA IN SOEBANDI JEMBER HOSPITAL - Rondhianto; Dini Kurniawati; Ayu Kurnia Vidiany (NurseLine Journal, 2016)
Surgery is one of procedur to cure of the disease with method cut and slice of the body. Almost surgery use general aenesthesia before the procedure began. After general anes thesia procedure, the acumulation of mucus secretion in respiratory tract have occured. The accamulatin of mucus secretion it it cause by intubation endotracheal tube proce dure or effect of anesthetic agens itself. The mucus accumulation can lead improving of